421 Initial results of a phase 1 trial of RP2, a first in class, enhanced potency, anti-CTLA-4 antibody expressing, oncolytic HSV as single agent and combined with nivolumab in patients with solid tumors. (10th December 2020) - Aroldi, Francesca; Sacco, Joseph; Harrington, Kevin; Olsson-Brown, Anna; Nanclares, Pablo; Menezes, Lavita; Bommareddy, Praveen; Thomas, Suzanne; Kaufman, Howard; Samakoglu, Selda; Coffin, Robert; Middleton, Mark
Abstract : Background: RP2 is an enhanced potency oncolytic HSV-1 expressing granulocyte-macrophage colony-stimulating factor (GM-CSF), a fusogenic protein (GALV-GP R-), and an anti-cytotoxic T lymphocyte antigen 4 (CTLA-4) antibody-like molecule which is being tested in an open-label, multicenter, phase 1 study alone and combined with PD-1 blockade (NCT04336241 ). Methods: The objectives were to assess initial safety and efficacy and determine the recommended phase 2 dose (RP2D) of RP2 alone and combined with nivolumab. Patients were to be treated using a 3+3 dose escalation at two dose levels of up to 10 mL of RP2 Q2W up to 5 times (dose level 1: 10 5 PFU/mL then 4 doses of 10 6 PFU/mL; dose level 2: 10 6 PFU/mL then 4 doses of 10 7 PFU/mL). Following determination of the RP2D, additional HSV-1 seronegative patients were to be enrolled such that ≥3 had been dosed with RP2 at the RP2D, and a combination cohort of up to 30 patients dosed up to 8 times with RP2 at the RP2D combined with nivolumab (240 mg Q2W for 4 months from the second RP2 dose, then 480 mg Q4W for 20 months) opened. Lesions were injected directly or under imaging guidance used for visceral lesions. Tumor biopsies were obtained for biomarker analysis. Viral shedding and anti-HSV antibody titers were also monitored. Results: Six HSV seropositive patients were enrolled in the dose-escalation phase with primarily Grade 1–2 adverse events, including febrile and other constitutional symptoms, local inflammation, and erythema observed. There were no DLTs requiring dose level expansion. The RP2D was selected as up to 10 mL of 10 6 PFU/mL followed Q2W by multiple doses of 10 7 PFU/mL. Of the six patients treated with single agent RP2, three (50%) have ongoing partial responses. Objective responses (including in uninjected tumors) were observed in patients with uveal melanoma (prior ipilumumab/nivolumab; extensive liver metastases), mucoepidermoid carcinoma (prior carboplatin/paclitaxel, bicalutamide, ceralasertib), and esophageal cancer (prior durvalumab, M6620, capecitabine, oxaliplatin, cisplatin, chemoradiation; liver and abdominal node metastases). Enrollment is underway in HSV seronegative patients and in combination with nivolumab. Updated data including biomarker and biodistribution data will be presented. Conclusions: The Phase 1 clinical data supports the safety and efficacy of single agent RP2, including demonstration of uninjected tumor response in patients with difficult to treat advanced cancers. This data supports the hypothesis that anti-CTLA-4 delivered intra-tumorally through oncolytic virus replication, with accompanying antigen release and presentation, can provide potent anti-tumor effects.